New records of riddles and folk-lore traditions of Russian settlements on the territory of the Lithuanian SSR - Mitropolskaya, N. M. (Literatūra, 1974)
The settlements of Russian natives who, owing to the force of different circumstances, made their home in various parts of the Lithuanian SSR are three hundred years old. Living in islands among the natives who speak another language, they maintain the Russian folk-lore tradition by national oral poetry. The study of the materials of the folk-lore expeditions which took place in 1960–1971 and which are kept in the archives of the Chair of the Russian literature of the Vilnius State University enables us to find out the peculiarities of occurrences and the character of the native multi-genre repertoire. A special study of the records of 820 riddles which exist in oral form enabled us to establish their numerous variants and types, to discover unique and original texts with subtle feeling for words, consonance and rhythm. The beautiful specimens of the riddles recorded for the first time in this locality keep and cherish for people the poetical beauty of nature and everyday life and the greatest resources of the folk word. They deserve a worthy place in the all-Russian collection of riddles.